2010
DOI: 10.1007/128_2010_69
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Programmed Polymers for Targeted DNA and siRNA Transfection

Abstract: Plasmid DNA and siRNA have a large potential for use as therapeutic nucleic acids in medicine. The way to the target cell and its proper compartment is full of obstacles. Polymeric carriers help to overcome the encountered barriers. Cationic polymers can interact with the nucleic acid in a nondamaging way but still require optimization with regard to transfer efficiency and biocompatibility. Aiming at viruslike features, as viruses are the most efficient natural gene carriers, the design of bioresponsive polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 155 publications
0
22
0
Order By: Relevance
“…The PEGylation of (hy)PEI is typically accomplished using chemical bonds which are relatively stable in the intracellular environment . The lack of biodegradability of (hy)PEI‐g‐PEG block copolymers prevents timely release of internalized DNA from the complex due to steric interferences of the still associated PEG chains . Furthermore, steric interference of PEG chains reduces PEI's ability to condense DNA into a compact polyplex particle, which coincidently reduces the polyplex micelles' stability in the presence of competing polyanions such as glycosaminoglycans .…”
Section: Introductionmentioning
confidence: 99%
“…The PEGylation of (hy)PEI is typically accomplished using chemical bonds which are relatively stable in the intracellular environment . The lack of biodegradability of (hy)PEI‐g‐PEG block copolymers prevents timely release of internalized DNA from the complex due to steric interferences of the still associated PEG chains . Furthermore, steric interference of PEG chains reduces PEI's ability to condense DNA into a compact polyplex particle, which coincidently reduces the polyplex micelles' stability in the presence of competing polyanions such as glycosaminoglycans .…”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of siRNA molecules can be incorporated into polymer delivery carriers, and enhanced transfection can occur when compared to plasmid DNA for example (Salcher and Wagner, 2010). Silencing RNA technology is rapidly advancing to the clinic (Davis, 2010) and is being applied to the ear (Alvarado et al, 2011, Maeda et al, 2005, Mukherjea et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…[275,297] PEI unfortunately displays serious toxic effects and the repeated systemic application as a gene carrier is limited due to the fact that it is nonbiodegradable. [298] Therefore, when designing a new carrier to achieve efficient condensation and cytosolic release with low toxicity, the carrier should be degradable. Various efficient polymers bearing hydrolyzable ester bonds have been designed, whereas the degradable linker is either integrated in the polymer backbone or serves as a cross-linking agent.…”
Section: Ph-responsive Dendritic Nanocarriersmentioning
confidence: 99%
“…Various efficient polymers bearing hydrolyzable ester bonds have been designed, whereas the degradable linker is either integrated in the polymer backbone or serves as a cross-linking agent. [298] Many research groups generate biodegradable polycations, e.g., by cross-linking nontoxic low molecular weight monomers or oligomers with linkers containing labile bonds. Green et al [117,300] reported, e.g., poly(β-amino ester)s as promising materials because they bind and self-assemble with DNA to form stable nanoparticles that effectively enter cells, escape the endosomal compartments, and degrade via hydrolytic cleavage of backbone ester groups.…”
Section: Ph-responsive Dendritic Nanocarriersmentioning
confidence: 99%